2020
DOI: 10.1371/journal.pcbi.1008272
|View full text |Cite
|
Sign up to set email alerts
|

Visually guided homing of bumblebees in ambiguous situations: A behavioural and modelling study

Abstract: Returning home is a crucial task accomplished daily by many animals, including humans. Because of their tiny brains, insects, like bees or ants, are good study models for efficient navigation strategies. Bees and ants are known to rely mainly on learned visual information about the nest surroundings to pinpoint their barely visible nest-entrance. During the return, when the actual sight of the insect matches the learned information, the insect is easily guided home. Occasionally, modifications to the visual en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 65 publications
(118 reference statements)
0
25
0
Order By: Relevance
“…However, we can extend it to trajectories that do not form routes. For example, animals may steer in a given direction to go away from a food source and hide its collected reward (e.g., dung beetle, Dacke et al, 2013 ), move in a convoluted manners to avoid a predator or chase prey (Boeddeker et al, 2003 ; Kane and Zamani, 2014 ; Wardill et al, 2017 ) or perform complex search behavior when searching for home (Doussot et al, 2020 ; Schultheiss et al, 2015 ). In these examples, the animals are not following a route.…”
Section: Discussionmentioning
confidence: 99%
“…However, we can extend it to trajectories that do not form routes. For example, animals may steer in a given direction to go away from a food source and hide its collected reward (e.g., dung beetle, Dacke et al, 2013 ), move in a convoluted manners to avoid a predator or chase prey (Boeddeker et al, 2003 ; Kane and Zamani, 2014 ; Wardill et al, 2017 ) or perform complex search behavior when searching for home (Doussot et al, 2020 ; Schultheiss et al, 2015 ). In these examples, the animals are not following a route.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, several modeling analyses showed that to enable successful homing, there is no need to know the exact location in space where the bee memorizes environmental information, such as a panoramic-snapshot (Dewar et al, 2014 ; Doussot et al, 2020a ). These models solely require the memorized panoramic-snapshots to be oriented toward the nest-hole.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, insects also rely on view-matching in the final approach to their nest (Zeil, 2012 ; Webb, 2019 ; Sun et al, 2020 ). An insect is thought to compare its current retinotopic representation of the environment with one or several previously-stored views of its nest surroundings (Doussot et al, 2020a ). These views might be learned during its early trips out of the nest, when naïve to the visual surroundings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural studies showed that views close to the goal are acquired during learning walks or flight [11,42] and modelling studies could emphasise the successful use during homing [12,14,13] for the memorised snapshots (eight positions taken either outside or inside the clutter and either above the clutter, bird's eye view, or close to the ground, frog's eye views). A&B: Examples of panoramic snapshots in A from the bird's eye view outside the clutter and in B frog's eye views inside the clutter.…”
Section: Positions Of Snapshots)mentioning
confidence: 99%